The Modernization of a Historic City as the Construction of a Soviet Utopia: Case of Vilnius - Rožėnė, Rugilė (Lietuvos istorijos studijos, 2021)
The article looks at urban planning and construction processes in Vilnius during the Soviet era from a point of view that has not been widely explored in the existing historiography. The approach is based on analysing relations between the existing city and the city-in-construction within the context of Soviet urban modernisation. Interpreting the communist city as a utopia, the analysis looks at its role in shaping negative attitudes towards the historic city as well as what tangible forms this utopia assumes in the process of being realised. The article argues that this process, purportedly a rational way towards the utopia and characterised by a fragmentary implementation of development projects, is one of the main factors behind the disintegration of the urban space in the Soviet era.
Keywords: utopia; Soviet modernisation; city planning; construction